Truncating mutations in the last exon of NOTCH3 cause lateral meningocele syndrome. - Gripp, Karen W; Robbins, Katherine M; Sobreira, Nara L; Witmer, P Dane; Bird, Lynne M; Avela, Kristiina; Mäkitie, Outi; Alves, Daniela; Hogue, Jacob S; Zackai, Elaine H; Doheny, Kimberly F; Stabley, Deborah L; et al. (Am J Med Genet A, 2015)
Lateral meningocele syndrome (LMS, OMIM%130720), also known as Lehman syndrome, is a very rare skeletal disorder with facial anomalies, hypotonia and meningocele-related neurologic dysfunction. The characteristic lateral meningoceles represent the severe end of the dural ectasia spectrum and are typically most severe in the lower spine. Facial features of LMS include hypertelorism and telecanthus, high arched eyebrows, ptosis, midfacial hypoplasia, micrognathia, high and narrow palate, low-set ears and a hypotonic appearance. Hyperextensibility, hernias and scoliosis reflect a connective tissue abnormality, and aortic dilation, a high-pitched nasal voice, wormian bones and osteolysis may be present. Lateral meningocele syndrome has phenotypic overlap with Hajdu-Cheney syndrome. We performed exome resequencing in five unrelated individuals with LMS and identified heterozygous truncating NOTCH3 mutations. In an additional unrelated individual Sanger sequencing revealed a deleterious variant in the same exon 33. In total, five novel de novo NOTCH3 mutations were identified in six unrelated patients. One had a 26 bp deletion (c.6461_6486del, p.G2154fsTer78), two carried the same single base pair insertion (c.6692_93insC, p.P2231fsTer11), and three individuals had a nonsense point mutation at c.6247A > T (pK2083*), c.6663C > G (p.Y2221*) or c.6732C > A, (p.Y2244*). All mutations cluster into the last coding exon, resulting in premature termination of the protein and truncation of the negative regulatory proline-glutamate-serine-threonine rich PEST domain. Our results suggest that mutant mRNA products escape nonsense mediated decay. The truncated NOTCH3 may cause gain-of-function through decreased clearance of the active intracellular product, resembling NOTCH2 mutations in the clinically related Hajdu-Cheney syndrome and contrasting the NOTCH3 missense mutations causing CADASIL.
Keywords: Abnormalities, Multiple; Child; Child, Preschool; DNA Mutational Analysis; Exome; Exons; Facies; High-Throughput Nucleotide Sequencing; Humans; Magnetic Resonance Imaging; Male; Meningocele; Mutation; Phenotype; Receptor, Notch3; Receptors, Notch; Young Adult

A recurrent PDGFRB mutation causes familial infantile myofibromatosis. - Cheung, Yee Him; Gayden, Tenzin; Campeau, Philippe M; LeDuc, Charles A; Russo, Donna; Nguyen, Van-Hung; Guo, Jiancheng; Qi, Ming; Guan, Yanfang; Albrecht, Steffen; Moroz, Brenda; Eldin, Karen W; et al. (Am J Hum Genet, 2013)
Infantile myofibromatosis (IM) is the most common benign fibrous tumor of soft tissues affecting young children. By using whole-exome sequencing, RNA sequencing, and targeted sequencing, we investigated germline and tumor DNA in individuals from four distinct families with the familial form of IM and in five simplex IM cases with no previous family history of this disease. We identified a germline mutation c.1681C>T (p.Arg561Cys) in platelet-derived growth factor receptor β (PDGFRB) in all 11 affected individuals with familial IM, although none of the five individuals with nonfamilial IM had mutations in this gene. We further identified a second heterozygous mutation in PDGFRB in two myofibromas from one of the affected familial cases, indicative of a potential second hit in this gene in the tumor. PDGFR-β promotes growth of mesenchymal cells, including blood vessels and smooth muscles, which are affected in IM. Our findings indicate p.Arg561Cys substitution in PDGFR-β as a cause of the dominant form of this disease. They provide a rationale for further investigations of this specific mutation and gene to assess the benefits of targeted therapies against PDGFR-β in aggressive life-threatening familial forms of the disease.
Keywords: Amino Acid Sequence; Female; Genes, Dominant; Genetic Association Studies; Germ-Line Mutation; Heterozygote; Humans; Male; Models, Molecular; Mutation, Missense; Myofibromatosis; Pedigree; Protein Structure, Tertiary; Receptor, Notch3; Receptor, Platelet-Derived Growth Factor beta; Receptors, Notch; Sequence Analysis, DNA